2018
DOI: 10.1002/lary.27441
|View full text |Cite
|
Sign up to set email alerts
|

Development of a survival animal model for subglottic stenosis

Abstract: NA. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…The result showed that all the 37 patients underwent T-tube placement the first time in treating airway stenosis and the treatment period was at least 10 months, with an extubating rate of 83.7%, demonstrating the effectiveness of T-tube placement in treating cervical airway stenosis [13]. Furthermore, an experiment induced subglottic stenosis in animal models, and its results showed that endoscopic intervention treatment for subglottic stenosis is well instructive [14], which is of guiding significance for future intervention treatment with endoscopy for airway stenosis. Our study was targeted to patients with Cotton-Myer IV subglottic airway stenosis and retrospectively explored the effectiveness and safety of T-tube placement in treating subglottic airway stenosis with a rigid bronchoscope after bi-level airway recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that all the 37 patients underwent T-tube placement the first time in treating airway stenosis and the treatment period was at least 10 months, with an extubating rate of 83.7%, demonstrating the effectiveness of T-tube placement in treating cervical airway stenosis [13]. Furthermore, an experiment induced subglottic stenosis in animal models, and its results showed that endoscopic intervention treatment for subglottic stenosis is well instructive [14], which is of guiding significance for future intervention treatment with endoscopy for airway stenosis. Our study was targeted to patients with Cotton-Myer IV subglottic airway stenosis and retrospectively explored the effectiveness and safety of T-tube placement in treating subglottic airway stenosis with a rigid bronchoscope after bi-level airway recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described in the literature, the brush was trimmed to maintain 10 mm of nylon bristles at the distal tip of the wire and rotated an average of 40 times along the subglottic mucosa to create the epithelial injury. 19 To minimize collateral trauma upon insertion, a modified Seldinger technique was employed by telescoping a 3.5-mm uncuffed ETT over the nylon brush. Though the technique improved unwanted mucosal trauma, particularly in the glottis, we found the method cumbersome to perform under direct visualization with endoscopy, at least for a 2-handed, 1-surgeon technique.…”
Section: Methodsmentioning
confidence: 99%
“…Endoscopic methods for injury, including endotracheal intubation and cautery, are widely described, with success in producing low to moderate stenosis (grade 1 or 2). 19 These current models, however, remain limited by high mortality and morbidity, large variability in the degree of stenosis, and subjectivity of the endoscopic stenosis grading methods. [20][21][22][23] A critical preclinical approach in understanding the biology of SGS and translating investigative technologies from the bench to the bedside is the use of these rabbit models.…”
mentioning
confidence: 99%
“…Subglottic stenosis induction was carried out following a previously described protocol . Bugbee monopolar cautery was inserted under endoscopic visualization and used to injure 75% of the circumference of the posterior subglottic area with 7 watts of power for approximately 5 seconds.…”
Section: Methodsmentioning
confidence: 99%